2010
DOI: 10.1614/ipsm-d-09-00047.1
|View full text |Cite
|
Sign up to set email alerts
|

Public Reaction to Invasive Plant Species in a Disturbed Colorado Landscape

Abstract: Invasive plant species degrade ecosystems in many ways. Controlling invasive plants is costly for government agencies, businesses, and individuals. North central Colorado is currently experiencing large-scale disturbance, and millions of acres are vulnerable to invasion because of natural and socioeconomic processes. Mountain pine beetles typically endemic to this region have reached epidemic proportions, with up to 80% tree mortality, which opens growing space for invasive plants. In socioeconomic terms, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 74 publications
(25 reference statements)
3
19
0
Order By: Relevance
“…Our results resembled those of Daab and Flint's (2010) study of the general public in Colorado, who also agreed that invasive plants were a concern. Our stakeholder groups differed somewhat in how strongly they perceived invasive plants to be a problem.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Our results resembled those of Daab and Flint's (2010) study of the general public in Colorado, who also agreed that invasive plants were a concern. Our stakeholder groups differed somewhat in how strongly they perceived invasive plants to be a problem.…”
Section: Discussionsupporting
confidence: 87%
“…Colton and Alpert (1998) concluded that public awareness and understanding of biological invasions by plants was poor, and Steele et al (2006) found that only 34% of West Virginia woodland landowner respondents had heard or read information about invasive plants. However, more recently Daab and Flint (2010) reported 88% of the general public in Colorado had heard or read about invasive plants. Our respondents in Iowa were very aware of the term ''invasive plant,'' and the majority also demonstrated comprehension of its meaning with their write-in answers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study (Hunter 2011) on local residents' responses to the loss of street trees from Emerald Ash Borer in Michigan did not actively assess levels of awareness but the study does highlight that proximity to tree loss had an impact on residents increasing their engagement with stewardship activities. Daab and Flint (2010) investigated awareness of the spread of invasive plants following an outbreak of MPB in Colorado (Daab and Flint 2010). The authors surveyed 1,346 residents across nine communities in north-central Colorado.…”
Section: Local Residentsmentioning
confidence: 99%
“…For example, 68 % of consumers in horticultural-oriented internet discussion forums that were familiar with the issues around invasive plants had read about them in magazines and newspapers (Reichard and White 2001), while plantbuyers surveyed by Kelley et al (2006) first found out about invasive plants via television (27.4 %), newspapers, magazines and books (19.8 %), friends, family and neighbours (9.4 %), garden clubs (7.5 %) and garden centres and nurseries (7.1 %). Daab and Flint (2010) found that the most common source of information on invasive plants for residents in North Colorado was newspapers (67.8 %), followed by 'word of mouth' (50.3 %), 'my own observations' (49.5 %) and the 'County extension office' (38.2 %). Twelve further sources of information were identified by this study.…”
Section: Information Provision and Stakeholder Engagementmentioning
confidence: 99%